Mental Health Trends in the 60-Year-Old Elderly Analyzing Scopus Bibliometric Database and WHO Guidelines for the Period 2010-2025 - Wasa, Carolus; Yambedoan, Thadius; Sumarsono, Adi; Lewar, Emanuel; Marlissa, Damaris; Yuliana, Roma (JUMORA: Jurnal Moderasi Olahraga, 2025)
The increase in life expectancy globally has led to a significant increase in the elderly population, including those aged 60 years and over. This condition requires special attention to various aspects of elderly welfare, one of which is mental health. Elderly mental health is a crucial issue due to various factors such as social isolation, unstable economic conditions, and limited access to mental health services. The World Health Organization (WHO) in its guidelines for 2010-2025 has emphasized the importance of a multidisciplinary approach in improving the quality of life of the elderly, including social and economic aspects that play an important role in determining well-being. The Scopus database-based bibliometric analysis method is one of the largest sources of scientific information covering various disciplines. The results of the analysis show that research on elderly mental health has increased significantly in the last decade, especially after the increasing global awareness of the importance of mental health in the elderly population. The main topics referred to in this study include the International Journal of Environmental Research and Public Health, BMJ Open Sport and Latihan Medicine, Frontiers in Psychology, Journal of Physical Education and Sport, and the British Journal of Sports Medicine. These journals publish various studies that examine how social and economic factors affect the mental health of the elderly